PENGUATAN PROFIL PELAJAR PANCASILA DAN RAHMATAN LIL ALAMIN PADA ELEMEN AKIDAH AKHLAK KELAS 4 DI MADRASAH IBTIDAIYAH MUHAMMADIYAH 27 SURABAYA - Hafiyah, Hidayatul (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2024)
Strengthening the Pancasila Student Profile and Rahmatan Lil Alamin Student Profile (PPRA) is a government initiative to strengthen understanding of Pancasila values ​​and Islamic teachings among students in order to face various complex challenges in education in Indonesia. The research entitled Strengthening the Pancasila and Rahmatan Lil Alamin Student Project on Elements of Moral Aqidah Class IV Madrasah Ibtidaiyah Muhammadiyah 27 Surabaya aims to describe and analyze the Learning of Moral Aqidah, Implementation, and the impact felt in the implementation of the Pancasila and Rahmatan Lil Alamin Student Profile. This research is qualitative research with a case study approach. The subjects of this research were the Head of Madrasah, Aqidah Akhlak Teacher, Curriculum Team, class IV students at MI Muhammadiyah 27 Surabaya. The object of this research is the Strengthening of the Pancasila and Rahmatan Lil Alamin Student Project on the Elements of Moral Creeds for Class IV Madrasah Ibtidaiyah Muhammadiyah 27 Surabaya. The methods used in this research are observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, drawing conclusions. The research results show that: 1) Strengthening the Pancasila and Rahmatan Lil Alamin Student Profile on the Aqidah Akhlak elements was designed through careful planning stages, involving a team of facilitators, identifying madrasah readiness. 2) The inhibiting factors are lack of training for teachers and lack of outreach to parents regarding the independent curriculum. 3) Supporting factors, namely the full commitment and support of the madrasa head, teachers and school staff in carrying out the program. Penguatan Profil Pelajar Pancasila dan Profil Pelajar Rahmatan Lil Alamin (PPRA) merupakan inisiatif pemerintah untuk memperkuat pemahaman nilai-nilai pancasila dan ajaran islam di kalangan pelajar guna menghadapi berbagai tantangan kompleks dalam pendidikan di Indonesia. Penelitian berjudul Penguatan Projek Pelajar Pancasila dan Rahmatan Lil Alamin Pada Elemen Akidah Akhlak Kelas IV Madrasah Ibtidaiyah Muhammadiyah 27 Surabaya ini bertujuan untuk mendeskripsikan serta menganalisis Pembelajaran Akidah Akhlak, Pelaksanaan, dan dampak yang dirasakan dalam pelaksanaan Profil Pelajar Pancasila dan Rahmatan Lil Alamin. Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus. Subjek penelitian ini adalah Kepala Madrasah, Guru Akidah Akhlak, Tim Kurikulum, siswa kelas IV MI Muhammadiyah 27 Surabaya. Objek penelitian ini adalah Penguatan Projek Pelajar Pancasila dan Rahmatan Lil Alamin Pada Elemen Akidah Akhlak Kelas IV Madrasah Ibtidaiyah Muhammadiyah 27 Surabaya. Metode yang digunakan dalam penelitian ini adalah observasi, wawancara, dan dokumentasi. Teknik analisis data meliputi reduksi data, penyajian data, penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: 1) Penguatan Profil Pelajar Pancasila dan Rahmatan Lil Alamin pada elemen Akidah Akhlak dirancang melalui tahapan perencanaan yang matang, dengan melibatkan tim fasilitator, mengidentifikasi kesiapan madrasah. 2) Faktor penghambat yaitu kurangnya pelatihan untuk guru dan kurangnya sosialisasi kepada wali murid mengenai kurikulum merdeka. 3) Faktor pendukung yaitu adanya komitmen dan dukungan penuh dari kepala madrasah, guru, dan staff sekolah dalam menjalankan program.